2019
DOI: 10.1111/ejn.14411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute total sleep deprivation on plasma melatonin, cortisol and metabolite rhythms in females

Abstract: Disruption to sleep and circadian rhythms can impact on metabolism. The study aimed to investigate the effect of acute sleep deprivation on plasma melatonin, cortisol and metabolites, to increase understanding of the metabolic pathways involved in sleep/wake regulation processes. Twelve healthy young female participants remained in controlled laboratory conditions for ~92 hr with respect to posture, meals and environmental light (18:00–23:00 hr and 07:00‐09:00 hr <8 lux; 23:00–07:00 hr 0 lux (sleep opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 85 publications
4
43
2
3
Order By: Relevance
“…These discrepancies could be explained by possible methodological limitations which might prevent an accurate assessment of the effect of sleep deprivation on cortisol release rhythmicity. However, and interestingly, some studies also failed to show a change in the HPA axis activity following total sleep deprivation when the experimental conditions were designed to avoid stress [55][56][57]. This shed light on the potential confounding effects of stress per se in sleep-deprivation experiments.…”
Section: Is Sleep Deprivation Stressful?mentioning
confidence: 99%
“…These discrepancies could be explained by possible methodological limitations which might prevent an accurate assessment of the effect of sleep deprivation on cortisol release rhythmicity. However, and interestingly, some studies also failed to show a change in the HPA axis activity following total sleep deprivation when the experimental conditions were designed to avoid stress [55][56][57]. This shed light on the potential confounding effects of stress per se in sleep-deprivation experiments.…”
Section: Is Sleep Deprivation Stressful?mentioning
confidence: 99%
“…Only positive mode reverse phase MS1 data were collected. Future work should take a targeted approach such as the Biocrates Absolute IDQ kits used in similar research ( 26 ). The metabolite identification reported here is preliminary and should be confirmed in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple circadian metabolites have been reported in the literature, identified with mass spectrometry-based metabolomics ( 22 24 ). Alterations to circadian rhythms in the metabolome have been documented in shift work ( 25 ) and sleep disruption protocols ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consolidating the role of circadian misalignment in development of metabolic disease, chronic sleep deprivation and simulated shifted work in healthy subjects have been shown to cause reduced glucose tolerance [419][420][421] and insulin resistance [402,422,423]. Moreover, induced circadian misalignment resulted in perturbed glucose tolerance and metabolite rhythms [402,[424][425][426][427]. Noteworthy, and in line with studies based on the laboratory protocols of sleep deprivation and shifted activity, observational studies in shift workers reported significantly increased risk of developing T2D that correlated with the number of night shifts per month [428].…”
Section: Circadian Clock Perturbation and Human Diseasesmentioning
confidence: 99%